Comprehensive assessment of the status of eroded soils in the Kharkiv region on the example of the erosion of the object «Mitrishin ravine» - Лисняк, А. А. (Man and Environment. Issues of Neoecology, 2014)
Presented are the results of field and analytical stages of studies on evaluation of the current state of eroded soils ravine-beam system «Мitrishin Ravine» Dergachi district, Kharkiv region. It is established that the soil cover in the studied areas is represented by variety of eroded and formed soil surface soil formation, and defined forest vegetative properties of soil data. It is shown that the lands of ravine-beam system «Мitrishin Ravine» currently runs at a constant process of soil formation, without the active manifestations of erosion processes, which is confirmed by the results of the analytical definitions of granulometric composition, the level of acidity, total humus and gross forms of NPK.